Complementarity of End Regions Increases the Lifetime of Small RNAs in Mammalian Cells - Koval, Anastasia P. (Public Library of Science, 2012)
Two RNAs (4.5SH and 4.5SI) with unknown functions share a number of features: short length (about 100 nt), transcription by RNA polymerase III, predominately nuclear localization, the presence in various tissues, and relatively narrow taxonomic distribution (4 and 3 rodent families, respectively). It was reported that 4.5SH RNA turns over rapidly, whereas 4.5SI RNA is stable in the cell, but their lifetimes remained unknown. We showed that 4.5SH is indeed short-lived (t(1/2)∼18 min) and 4.5SI is long-lived (t(1/2)∼22 h) in Krebs ascites carcinoma cells. The RNA structures specifying rapid or slow decay of different small cellular RNAs remain unstudied. We searched for RNA structural features that determine the short lifetime of 4.5SH in comparison with the long lifetime of 4.5SI RNA. The sequences of genes of 4.5SH and 4.5SI RNAs were altered and human cells (HeLa) were transfected with these genes. The decay rate of the original and altered RNAs was measured. The complementarity of 16-nt end regions of 4.5SI RNA proved to contribute to its stability in cells, whereas the lack of such complementarity in 4.5SH RNA caused its rapid decay. Possible mechanisms of the phenomenon are discussed.